Synthesis and Evaluation of New Hydrazone Derivatives as Antibacterial - Mostafa Fayez Tawfeeq (Iraqi Journal of Pharmaceutical Sciences)
Bacterial infections are ongoing challenging due to resistance developed by infectious bacteria. So that many researches targeting designing new antibacterials are published annually. Heterocycles are important field in organic synthesis due to their biological activities. On the other hand Schiff base are also possessing wide range of pharmacological activities. Hybridization-combing two pharmacophores to form one molecule-is usual method in designing new drugs. The new compounds [heterocycles-hydrazones] derivative were synthesized through multi-steps procedure and characterized by thin layer chromatography and spectroscopically by ATR-FTIR and 1HNMR. Disk diffusion method was used to evaluate the antibacterial activities of the new compounds. The compounds showed weak activities against K. pneumoniae, and good activities against E. coli and S. aureus.